The complicated pursuit of democratic teaching. (December 2017) - Gibbs, Brian
This article describes one secondary social studies teacher's attempts to build a pedagogically democratic classroom. The teacher designs curriculum around large essential questions, connects content to the present lives of students, and creates space for students to make their own decisions and choices. The teacher is convinced that she has created a strong democratic space. Upon closer inspection, when given a choice, students consistently chose gender and ethnic alike teams. This raised difficult and complicated questions about what a democratic classroom is. The author concludes that issues of gender, race, and student reflection upon their choices about gender and race have to be a strongly and well-embedded part of democratic teaching .